1982
DOI: 10.1111/j.1365-2044.1982.tb01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia for Caesarean section

Abstract: SummaryThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(44 citation statements)
references
References 12 publications
0
39
0
2
Order By: Relevance
“…Uteroplacental perfusion is an important determinant of fetal wellbeing and untreated hypotension due to subarachnoid blockade is detrimental [28]. Hence, the benefit of HES in decreasing the incidence of hypotension is valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Uteroplacental perfusion is an important determinant of fetal wellbeing and untreated hypotension due to subarachnoid blockade is detrimental [28]. Hence, the benefit of HES in decreasing the incidence of hypotension is valuable.…”
Section: Discussionmentioning
confidence: 99%
“…A lower incidence and lesser degree of hypotension (which can be easily corrected with intravenous boluses of ephedrine) can theoretically confer benefits to the fetus. The clinically significant level of hypotension to appropriately trigger a correction is controversial and arbitrary [5,11]. In this study, we arbitrarily defined hypotension as a systolic blood pressure below 90 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…This raises concern for the effect of nifedipine and epidural anesthesia on maternal blood pressure in the normotensive parturient when maternal hypotension is well-known as a common complication after epidural block. Decreases in maternal blood pressure have been related to fetal hypoxia and acidosis [14]. Many studies demonstrated that hypotension secondary to nifedipine given for preterm labor in normotensive patients were minimal [15–17], but severe hypotension resulting in fetal death from nifedipine has been reported [18].…”
Section: Commentmentioning
confidence: 99%
“…The relationship of intraoperative maternal hypotension and fetal hypoxia/acidosis has been demonstrated in the parturient undergoing cesarean section [14]. Unlike a healthy full-term fetus undergoing cesarean section, the second-trimester fetuses undergoing SFLP are usually sick with cardiovascular compromise, related to anemia in the donor twin and cardiomyopathy in the recipient twin.…”
Section: Commentmentioning
confidence: 99%